Why People Procrastinate on Facebook: Case Study from Employed and Unemployed Facebook Users in Sri Lanka - U. G. C. Lakchan; G. C. Samaraweera; T. H. Rathnayake (Kelaniya Journal of Management)
Procrastination is the intentional postponing of a necessary or devoted task, which can have a number of adverse impacts, including distress, physiological health issues, poor work performance, and subpar academic success. The study aims to analyze and compare procrastination levels among employed and unemployed Facebook users, exploring the reasons behind their procrastination, which is crucial from both an economic and informational perspective. Additionally, it seeks to investigate the association between procrastination on Facebook and the users' education levels. The study also examines how procrastination on Facebook differs between males and females. Positivistic research Philosophy, deductive approach and explanatory research design were deployed for this study. The study used convenience sampling technique and, 300 employed and unemployed Facebook users were taken for analysis of Independent sample test, Anova test and post hoc-tukeys test. Accordingly, five factors namely notification features, immersive decision features, surveillance of presence, identification features, and interaction features were utilized to gauge the degree of procrastination. The findings of this study outlined the causes of procrastination and revealed a substantial difference between employed and unemployed Facebook users in terms of procrastination levels on social media sites. Additionally, results showed that there is a considerable variation between males and females too. The findings will provide a deep knowledge for marketers, psychologists and for academics as well.